Magnesium-based bone cement with sonodynamic / nano-enzyme antibiosis and piezoelectric osteogenesis functions and preparation method of magnesium-based bone cement
By adding manganese and cerium to magnesium-based bone cement to co-doped modified sodium niobate, combining acoustic dynamics and nanoenzyme antibacterial mechanisms, piezoelectric osteogenesis performance is enhanced, and the problems of insufficient osteogenesis activity and poor antibacterial effect of bone cement in the prior art are solved, and efficient bone defect repair is achieved.
Patent Information
- Application Number
- CN202411466549.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-21
- Publication Date
- 2025-03-04
AI Technical Summary
The existing magnesium phosphate bone cement has insufficient osteogenic activity during bone defect repair, and it is difficult to effectively inhibit bacterial infection, affecting the bone repair effect.
The modified sodium niobate was prepared by hydrothermal method and added to magnesium-based bone cement, combining acoustic dynamics and nanoenzyme antibacterial mechanisms to enhance piezoelectric osteogenic properties.
The effective combination of antibacterial and bone repair of magnesium-based bone cement at different ultrasound powers has been achieved, which has significantly improved the therapeutic effect of bone defect repair.
Smart Images

Figure CN119551722A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of biomedical materials, and in particular, relates to a magnesium-based bone cement having both sonodynamic / nanozyme antibacterial and piezoelectric osteogenesis properties and a preparation method thereof. Background Art
[0002] Bone defects caused by trauma, tumors, infections and other factors often need to be reconstructed through implants. Magnesium phosphate cement (MPC) has good coagulation, mechanics and certain osteogenesis, which makes it widely used in the repair of bone defects, but its osteogenic activity still needs to be strengthened. In addition, the process of bone defect repair is often accompanied by bacterial infection, which inhibits bone tissue regeneration. Therefore, a good bone repair material should have antibacterial function in addition to osteogenesis.
[0003] Human bone tissue is a natural piezoelectric material with piezoelectric effect. It can convert stress into electrical signals (charge / microcurrent), and plays a vital role in bone metabolism, development, growth, remodeling and repair. Inspired by the piezoelectric effect of bone tissue and the osteogenesis effect of electrical stimulation, the use of piezoelectric materials to generate electrical signals to stimulate cell response and promote bone regeneration has attracted widespread attention.
[0004] Sonodynamic therapy (SDT) is a non-invasive treatment strategy based on low-intensity ultrasound triggering sonosensitizers to produce ROS, causing bacterial oxidative damage and death. Due to its advantages such as deep tissue penetration, minimal tissue damage, controllability and non-invasiveness, and the fact that the generated ROS will not produce drug resistance, it provides a new way to effectively treat deep tissue infection diseases. However, the rapid recombination of the electron-hole pairs of sonosensitizers after separation leads to a low yield of ROS, which reduces the therapeutic effect of sonodynamic therapy. In recent years, piezoelectric materials have received widespread attention as sonosensitizers; sonosensitizers with piezoelectric effect can generate piezoelectric potential under ultrasound, thereby promoting the separation of carriers and increasing the yield of ROS.
[0005] The single use of sonodynamic antibacterial often has poor efficacy and is difficult to timely and thoroughly eliminate bacterial / biofilm infections. Nanozymes with peroxidase-like (POD) activity can convert H2O2 into ·OH, effectively synergizing sonodynamic antibacterial; nanozymes with catalase-like (CAT) activity can remove H2O2 and convert it into O2, improve the oxidative stress microenvironment, and thus promote tissue regeneration. However, the activity of traditional nanozymes is not high. Studies have shown that the piezoelectric effect can promote the valence state conversion of metal elements in nanozymes, thereby improving the activity of nanozymes.
[0006] Sodium niobate (NNO) is an inorganic piezoelectric material with good biological activity. However, its piezoelectric performance is low, and doping can destroy the symmetry of its crystal structure, thereby improving its piezoelectricity. Manganese and cerium have multiple valence states, which make it have POD-like and CAT-like activities. Therefore, by doping with manganese and cerium, not only can the piezoelectric acoustic dynamic performance of NNO be enhanced, but also its enzyme-like activity can be given. Summary of the invention
[0007] The purpose of the present invention is to provide a magnesium-based bone cement having both sonodynamic / nanozyme antibacterial and piezoelectric osteogenesis.
[0008] Another object of the present invention is to provide a method for preparing the magnesium-based bone cement having both sonodynamic / nanozyme antibacterial and piezoelectric osteogenesis.
[0009] In order to achieve the above object, the technical solution adopted by the present invention is as follows:
[0010] The first aspect of the present invention provides a manganese-cerium co-doped modified sodium niobate, which is made of Nb2O5, MnO2, CeO2 and sodium hydroxide, and the molar ratio of Nb2O5, MnO2 and CeO2 is 1:0.01~0.2:0.01~0.2 (preferably 1:0.06:0.06, 1:0.1:0.08, 1:0.08:0.08, 1:0.1:0.1, 1:0.08:0.1); the molar ratio of Nb2O5 and sodium hydroxide is 1:1~50 (preferably 1:26.6).
[0011] The second aspect of the present invention provides a method for preparing the manganese-cerium co-doped modified sodium niobate, comprising the following steps: grinding and mixing Nb2O5, MnO2 and CeO2 in a molar ratio of 1:0.01-0.2:0.01-0.2 (preferably 1:0.06:0.06, 1:0.1:0.08, 1:0.08:0.08, 1:0.1:0.1, 1:0.08:0.1) uniformly, dissolving in a sodium hydroxide solution with a concentration of 1-5 mol / L (preferably 2 mol / L), the molar ratio of Nb2O5 to sodium hydroxide being 1:1-50 (preferably 1:26.6), stirring to a uniform suspension, reacting at a temperature of 150-200°C (preferably 160°C) for 1-16h (preferably 12h), washing, drying and calcining to obtain the manganese-cerium co-doped modified sodium niobate.
[0012] The drying conditions are as follows: drying at a temperature of 50 to 80° C. (preferably 60° C.) for 1 to 24 hours (preferably 24 hours).
[0013] The calcination conditions are as follows: calcination at a temperature of 350 to 500° C. (preferably 400° C.) for 0.5 to 2 h (preferably 1 h).
[0014] The third aspect of the present invention provides a magnesium-based bone cement with both sonodynamic / nanozyme antibacterial and piezoelectric osteogenesis, which is made of CaHPO4, NaH2PO4, MgO powder, hydroxyapatite (HA), and manganese-cerium co-doped modified sodium niobate, the molar ratio of CaHPO4, NaH2PO4 and MgO is 1-4:1-4:1 (preferably 2:2:1), the mass of hydroxyapatite (HA) accounts for 5-20wt% (preferably 10wt%) of the total mass of CaHPO4, NaH2PO4 and MgO, and the mass of manganese-cerium co-doped modified sodium niobate accounts for 5-40wt% (preferably 20wt%, 40wt%) of the total mass of CaHPO4, NaH2PO4, MgO, hydroxyapatite and manganese-cerium co-doped modified sodium niobate.
[0015] In a fourth aspect of the present invention, a method for preparing the magnesium-based bone cement having both sonodynamic / nanozyme antibacterial and piezoelectric osteogenesis is provided, comprising the following steps: mixing CaHPO4, NaH2PO4 and MgO powders in a molar ratio of 1 to 4:1 to 4:1 (preferably 2:2:1), adding hydroxyapatite (HA) and mixing evenly, wherein the mass of hydroxyapatite (HA) accounts for 5 to 20 wt% (preferably 10 wt%) of the total mass of CaHPO4, NaH2PO4 and MgO, and mixing the obtained mixture. The powder is evenly mixed with manganese-cerium co-doped modified sodium niobate, the mass percentage of manganese-cerium co-doped modified sodium niobate to the total mass of CaHPO4, NaH2PO4, MgO, hydroxyapatite and manganese-cerium co-doped modified sodium niobate is 5-40wt% (preferably 20wt%, 40wt%), deionized water is added to make the liquid-solid ratio 1.5-3g / mL (preferably 1.8g / mL), the mixture is fully blended and filled into a mold for forming, and solidified to obtain the magnesium-based bone cement with both sonodynamic / nanozyme antibacterial and piezoelectric osteogenesis.
[0016] The curing conditions are as follows: the sample is placed in an incubator at a temperature of 37° C. and a humidity of 100% for curing for 1 to 72 hours (preferably 72 hours).
[0017] The fifth aspect of the present invention provides a use of the magnesium-based bone cement having both sonodynamic / nanozyme antibacterial and piezoelectric osteogenesis in the preparation of a bone repair scaffold.
[0018] The sixth aspect of the present invention provides a use of the magnesium-based bone cement having both sonodynamic / nanozyme antibacterial and piezoelectric osteogenesis in the preparation of bone repair materials or bone transplant materials.
[0019] Due to the adoption of the above technical solution, the present invention has the following advantages and beneficial effects:
[0020] The magnesium-based bone cement with both sonodynamic / nanozyme antibacterial and piezoelectric osteogenesis provided by the present invention has both piezoelectric enhanced sonodynamic and nanozyme synergistic antibacterial activity and piezoelectric osteogenesis activity, effectively removes bacteria / biofilms, achieves a combination of antibacterial and bone repair under different ultrasonic powers, effectively treats infected bone defects, and significantly improves the therapeutic effect of MPC-based bone repair materials. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 Schematic diagram of SEM images and EDS images of NNO, M4-NNO, C4-NNO and MC-NNO.
[0022] Figure 2 Schematic diagram of the XRD images and XPS full spectra of different samples (NNO, M-NNO, C-NNO and MC-NNO).
[0023] Figure 3 It is a schematic diagram of the PFM amplitude diagram, phase diagram, butterfly loop and phase hysteresis curve results of NNO and MC-NNO.
[0024] Figure 4 It is a schematic diagram of the EIS curves and transient acoustic current it curves of NNO, M-NNO, C-NNO and MC-NNO.
[0025] Figure 5 Schematic diagram of the UV-Vis-NIR diffuse reflectance spectra and Kubelka–Munk patterns of NNO, M-NNO, C-NNO and MC-NNO.
[0026] Figure 6 Schematic diagram of the XPS valence band spectra of NNO and MC-NNO.
[0027] Figure 7 It is a schematic diagram of the acoustic dynamic mechanism of the sample.
[0028] Figure 8 This is a schematic diagram of the effects of different manganese and cerium doping levels on the acoustic dynamic properties of the sample.
[0029] Fig. 9 The ESR spectra of ·OH and ·O2 produced by different samples - Schematic diagram of ESR spectrum.
[0030] Fig.10 Schematic diagram of the CAT activity (a) and POD activity (d) of different samples at pH = 7.4 and pH = 5.5, the CAT activity (b) and POD activity (e) of MC-NNO at different pH values, and the CAT (c, pH = 7.4) and POD (f, pH = 5.5) activities at different ultrasonic intensities.
[0031] Fig.11 It is a digital photo and SEM image schematic diagram of magnesium-based bone cement MPC / MCN-2 particles.
[0032] Fig.12 This is a schematic diagram of the acoustic dynamic performance results of magnesium-based bone cements with different compositions.
[0033] Fig.13 This is a schematic diagram of the activity data results of magnesium-based bone cements with different compositions at pH = 7.4.
[0034] Fig.14 Different samples at 0.5W / cm 2 Schematic diagram of the data results of open circuit voltage and short circuit current under ultrasound action.
[0035] Fig.15 It is a schematic diagram of the in vitro antimicrobial performance results after culturing different samples and under different culture conditions.
[0036] Fig.16 This is a schematic diagram of the effects of different components of magnesium-based bone cement on the proliferation of rat bone marrow stromal cells. DETAILED DESCRIPTION
[0037] In order to explain the present invention more clearly, the present invention is further described below in conjunction with preferred embodiments. It should be understood by those skilled in the art that the following specific description is illustrative rather than restrictive, and should not be used to limit the scope of protection of the present invention.
[0038] Example 1
[0039] Preparation of Mn-Ce Co-doped Sodium Niobate (MC-NNO) Piezoelectric Powder
[0040] Sodium niobate (NNO), manganese-doped sodium niobate (M-NNO), cerium-doped sodium niobate (C-NNO) and manganese-cerium co-doped sodium niobate (MC-NNO) were prepared by hydrothermal reaction method.
[0041] Niobium pentoxide (Nb2O5, Shanghai Xiaohuang Nanotechnology Co., Ltd.) (3.76×10 -3 mol, 1g) was dissolved in 50mL of 2mol / L sodium hydroxide (0.1mol, 4g) solution and stirred for half an hour until a uniform suspension was obtained. The suspension was transferred to a reactor and reacted at 160°C for 12h, washed with deionized water and anhydrous ethanol in turn, dried (60°C, 24h), and calcined in a muffle furnace at 400°C for 1h to remove crystal water, thereby obtaining 0.98g of sodium niobate (NNO).
[0042] 3-MnNNO, 4-MnNNO and 5-MnNNO were prepared according to the components in Table 1. The specific preparation method includes the following steps:
[0043] Nb2O5(3.76×10 -3 mol, 1g) and manganese dioxide (2.26×10 -4 mol, 19.6 mg) (MnO2, Shanghai Aladdin Biochemical Technology Co., Ltd.) was ground and mixed evenly, dissolved in 50 mL of 2 mol / L sodium hydroxide (0.1 mol, 4 g) solution, and stirred for half an hour until a uniform suspension was obtained. The suspension was transferred to a reactor, reacted at 160°C for 12 hours, washed with deionized water and anhydrous ethanol in turn, dried (60°C, 24 hours), calcined at 400°C in a muffle furnace for 1 hour to remove crystal water, and 1.01 g of manganese-doped sodium niobate (3-MnNNO, abbreviated as M3-NNO) was obtained.
[0044] Nb2O5(3.76×10 -3 mol, 1g) and manganese dioxide (3×10 -4 mol, 26.2mg) (MnO2, Shanghai Aladdin Biochemical Technology Co., Ltd.) was ground and mixed evenly, dissolved in 50mL of 2mol / L sodium hydroxide (0.1mol, 4g) solution, and stirred for half an hour until a uniform suspension was obtained. The suspension was transferred to a reactor, reacted at 160°C for 12h, washed with deionized water and anhydrous ethanol in turn, dried (60°C, 24h), calcined at 400°C in a muffle furnace for 1h to remove crystal water, and 1.01g of manganese-doped sodium niobate (4-MnNNO, abbreviated as M4-NNO) was obtained.
[0045] Nb2O5(3.76×10 -3 mol, 1g) and manganese dioxide (3.76×10 -4 mol, 32.7 mg) (MnO2, Shanghai Aladdin Biochemical Technology Co., Ltd.) was ground and mixed evenly, dissolved in 50 mL of 2 mol / L sodium hydroxide (0.1 mol, 4 g) solution, and stirred for half an hour until a uniform suspension was obtained. The suspension was transferred to a reactor, reacted at 160°C for 12 hours, washed with deionized water and anhydrous ethanol in turn, dried (60°C, 24 hours), calcined at 400°C in a muffle furnace for 1 hour to remove crystal water, and 1.02 g of manganese-doped sodium niobate (5-MnNNO, abbreviated as M5-NNO) was obtained.
[0046] Table 1 Mn single doping group
[0047]
[0048] 3-CeNNO, 4-CeNNO and 5-CeNNO were prepared according to the components in Table 2. The specific preparation method includes the following steps:
[0049] Nb2O5(3.76×10 -3 mol, 1g) and cerium dioxide (2.26×10 -4 mol, 38.8 mg) (CeO2, Shanghai Xiaohuang Nanotechnology Co., Ltd.) was ground and mixed evenly, dissolved in 50 mL of 2 mol / L sodium hydroxide (0.1 mol, 4 g) solution, and stirred for half an hour until a uniform suspension was obtained. The suspension was transferred to a reactor, reacted at 160°C for 12 h, washed with deionized water and anhydrous ethanol in turn, dried (60°C, 24 h), and calcined in a muffle furnace at 400°C for 1 h to remove crystal water, to obtain 1.01 g of cerium-doped sodium niobate (3-CeNNO, abbreviated as C3-NNO).
[0050] Nb2O5(3.76×10 -3 mol, 1g) and cerium dioxide (3×10 -4 mol, 51.8 mg) (CeO2, Shanghai Xiaohuang Nanotechnology Co., Ltd.) was ground and mixed evenly, dissolved in 50 mL of 2 mol / L sodium hydroxide (0.1 mol, 4 g) solution, and stirred for half an hour until a uniform suspension was obtained. The suspension was transferred to a reactor, reacted at 160°C for 12 h, washed with deionized water and anhydrous ethanol in turn, dried (60°C, 24 h), and calcined in a muffle furnace at 400°C for 1 h to remove crystal water, to obtain 1.04 g of cerium-doped sodium niobate (4-CeNNO, abbreviated as C4-NNO).
[0051] Nb2O5(3.76×10 -3 mol, 1g) and cerium dioxide (3.76×10 -4 mol, 64.7 mg) (CeO2, Shanghai Xiaohuang Nanotechnology Co., Ltd.) was ground and mixed evenly, dissolved in 50 mL of 2 mol / L sodium hydroxide (0.1 mol, 4 g) solution, and stirred for half an hour until a uniform suspension was obtained. The suspension was transferred to a reactor, reacted at 160°C for 12 h, washed with deionized water and anhydrous ethanol in turn, dried (60°C, 24 h), and calcined in a muffle furnace at 400°C for 1 h to remove crystal water, to obtain 1.08 g of cerium-doped sodium niobate (5-CeNNO, abbreviated as C5-NNO).
[0052] Table 2 Ce single doping group
[0053]
[0054] Manganese-cerium co-doped sodium niobate (MC-NNO) was prepared according to the components in Table 3. The specific preparation method includes the following steps:
[0055] Nb2O5(3.76×10-3 mol, 1g), MnO2(3×10 -4 mol, 26.2 mg) and CeO2 (3×10 -4 mol, 51.8 mg) was ground and mixed evenly, dissolved in 50 mL of 2 mol / L sodium hydroxide (0.1 mol, 4 g) solution, and stirred for half an hour until a uniform suspension was obtained. The suspension was transferred to a reactor, reacted at 160°C for 12 hours, washed with deionized water and anhydrous ethanol in turn, dried (60°C, 24 hours), calcined in a muffle furnace at 400°C for 1 hour to remove crystal water, and 1.06 g of manganese / cerium co-doped sodium niobate (abbreviated as MC-NNO) was obtained.
[0056] Table 3 Grouping of Mn / Ce co-doped samples
[0057]
[0058] According to the ratio in Table 4, the preparation method of magnesium-based bone cement MPC / MC-NNO with both sonodynamic / nanozyme antibacterial and piezoelectric osteogenesis includes the following steps:
[0059] CaHPO4 (0.01 mol, 1.36 g), NaH2PO4 (0.01 mol, 1.2 g) and MgO powder (5 × 10 -3 mol, 0.2 g) were mixed, the molar ratio of CaHPO4, NaH2PO4 and MgO was 2:2:1, and hydroxyapatite (HA) (5.5×10 -4 mol, 0.28g) were mixed evenly. The mass of hydroxyapatite accounted for 10wt% of the total mass of CaHPO4, NaH2PO4 and MgO. 1.69mL of deionized water was added to make the liquid-solid ratio 1.8g / mL, fully blended, filled into a polytetrafluoroethylene mold, and taken out after molding. The taken out sample was placed in an incubator with a temperature of 37°C and a humidity of 100% to cure for 72h, and 2.98g of magnesium-based bone cement MPC was obtained.
[0060] CaHPO4 (0.01 mol, 1.36 g), NaH2PO4 (0.01 mol, 1.2 g) and MgO powder (5 × 10 -3 mol, 0.2 g) were mixed, the molar ratio of CaHPO4, NaH2PO4 and MgO was 2:2:1, and hydroxyapatite (HA) (5.5×10 -4 mol, 0.28 g) were mixed evenly. The mass of hydroxyapatite accounted for 10 wt% of the total mass of CaHPO4, NaH2PO4 and MgO. The mixed powder obtained above was mixed with NNO (4.64×10 -3mol, 0.76g) were mixed evenly, the mass percentage of NNO in the total mass of CaHPO4, NaH2PO4, MgO, hydroxyapatite and NNO was 20%, 2.11mL of deionized water was added to make the liquid-solid ratio 1.8g / mL, fully blended, filled into a polytetrafluoroethylene mold, and taken out after molding. The taken out sample was placed in an incubator with a temperature of 37°C and a humidity of 100% for curing for 72h to obtain 3.73g of magnesium-based bone cement MPC / N-1.
[0061] CaHPO4 (0.01 mol, 1.36 g), NaH2PO4 (0.01 mol, 1.2 g) and MgO powder (5 × 10 -3 mol, 0.2 g) were mixed, the molar ratio of CaHPO4, NaH2PO4 and MgO was 2:2:1, and hydroxyapatite (HA) (5.5×10 -4 mol, 0.28 g) were mixed evenly. The mass of hydroxyapatite accounted for 10 wt% of the total mass of CaHPO4, NaH2PO4 and MgO. The mixed powder obtained above was mixed with NNO (1.23×10 -2 mol, 2.02g) were mixed evenly, the mass percentage of NNO in the total mass of CaHPO4, NaH2PO4, MgO, hydroxyapatite and NNO was 40%, 2.81mL of deionized water was added to make the liquid-solid ratio 1.8g / mL, fully blended, filled into a polytetrafluoroethylene mold, and taken out after molding. The taken out sample was placed in an incubator with a temperature of 37°C and a humidity of 100% for curing for 72h to obtain 4.98g of magnesium-based bone cement MPC / N-2.
[0062] CaHPO4 (0.01 mol, 1.36 g), NaH2PO4 (0.01 mol, 1.2 g) and MgO powder (5 × 10 -3 mol, 0.2 g) were mixed, the molar ratio of CaHPO4, NaH2PO4 and MgO was 2:2:1, and hydroxyapatite (HA) (5.5×10 -4 mol, 0.28 g) were mixed evenly. The mass of hydroxyapatite accounted for 10 wt% of the total mass of CaHPO4, NaH2PO4 and MgO. The mixed powder obtained above was mixed with MC-NNO (4.66×10 -3 mol, 0.76g) were mixed evenly, the mass percentage of MC-NNO in the total mass of CaHPO4, NaH2PO4, MgO, hydroxyapatite and MC-NNO was 20%, 2.11mL of deionized water was added to make the liquid-solid ratio 1.8g / mL, fully blended, filled into a polytetrafluoroethylene mold, and taken out after molding. The sample was placed in an incubator with a temperature of 37°C and a humidity of 100% for curing for 72h to obtain 3.71g of magnesium-based bone cement MPC / MCN-1.
[0063] CaHPO4 (0.01 mol, 1.36 g), NaH2PO4 (0.01 mol, 1.2 g) and MgO powder (5 × 10 -3 mol, 0.2 g) were mixed, the molar ratio of CaHPO4, NaH2PO4 and MgO was 2:2:1, and hydroxyapatite (HA) (5.5×10 -4 mol, 0.28 g) were mixed evenly. The mass of hydroxyapatite accounted for 10 wt% of the total mass of CaHPO4, NaH2PO4 and MgO. The mixed powder obtained above was mixed with MC-NNO (1.24×10 -2 mol, 2.02g) were mixed evenly, the mass percentage of MC-NNO in the total mass of CaHPO4, NaH2PO4, MgO, hydroxyapatite and MC-NNO was 40%, 2.81mL of deionized water was added to make the liquid-solid ratio 1.8g / mL, fully blended, filled into a polytetrafluoroethylene mold, and taken out after molding. The taken out sample was placed in an incubator with a temperature of 37°C and a humidity of 100% for curing for 72h to obtain 5.01g of magnesium-based bone cement MPC / MCN-2.
[0064] Table 4 Grouping of composite bone cement samples
[0065]
[0066]
[0067] 1. Characterize the physical and chemical properties of the samples prepared above:
[0068] The morphology of different powders was characterized by scanning electron microscopy (SEM, S4800, Hitachi, Japan). The crystal phase structure of different powders was characterized by X-ray diffraction (XRD, Bruker, Germany). The chemical state and valence band of different powders were characterized by X-ray photoelectron spectroscopy (XPS, 250Xi, Thermo Fisher Scientific, USA). The absorption spectra of different powders were characterized by UV-VIS-NIR spectrophotometer (Lambda950, Varian, USA), and the bandgap width of different powders was calculated by formula.
[0069] The electrochemical impedance, model Schottky curve and transient ultrasonic response current of different powders (NNO and doped NNO) were measured by a three-electrode system of an electrochemical workstation (CHI 660E, Shanghai Chenhua Instrument Co., Ltd., China). In the three-electrode system, the ITO conductive glass coated with powder was the working electrode, the saturated Ag / AgCl was the reference electrode, and the platinum sheet was the counter electrode; the electrolyte used was 0.5 M sodium sulfate solution.
[0070] In the accompanying drawings, M-NNO shown in the figure represents M4-NNO, and C-NNO shown in the figure represents C4-NNO.
[0071] Figure 1 The SEM images and EDS images of NNO, M4-NNO (M-NNO is shown in the figure), C4-NNO (C-NNO is shown in the figure) and MC-NNO are schematic diagrams. Among them, a is a schematic diagram of the SEM image, and b is a schematic diagram of the EDS image. The SEM image shows that NNO, M-NNO, C-NNO and MC-NNO are all cubic in appearance, and the particle diameter is about 500nm, indicating that the doped manganese and cerium form a good solid solution in NNO. The EDS image shows that Na, Nb and O are evenly distributed on all samples; compared with NNO, the element signals of Mn and Ce appear on the surface of M-NNO and C-NNO, respectively, and the signals of both Mn and Ce appear on MC-NNO, which can preliminarily prove that Mn and Ce are doped in MC-NNO.
[0072] Figure 2 Schematic diagram of XRD images and XPS full spectra of different samples (NNO, M-NNO, C-NNO and MC-NNO), where a is a schematic diagram of XRD images of different samples, b is a schematic diagram of XPS images of different samples, c is a schematic diagram of the core-level XPS spectrum of NNO-Nb 3d, d is a schematic diagram of the core-level XPS spectrum of NNO-O 1S, e is a schematic diagram of the core-level XPS spectrum of Nb 3d of MC-NNO, f is a schematic diagram of the core-level XPS spectrum of O1S of MC-NNO, g is a schematic diagram of the core-level XPS spectrum of Mn 2p of MC-NNO, h is a schematic diagram of the core-level XPS spectrum of Ce 3d of MC-NNO, O1 is lattice oxygen, O2 is defective oxygen, and O3 is adsorbed oxygen.
[0073] Figure 2 The XRD spectra of a show that NNO, M-NNO, C-NNO and MC-NNO are all orthorhombic phase structures, and doping with Mn and Ce does not change the crystal form of NNO. The full XPS spectra of NNO and MC-NNO ( Figure 2 (b) shows that: Na, Nb, and O element peaks appear in both MC-NNO and NNO; compared with NNO, MC-NNO also has Ce and Mn element peaks, indicating that MC-NNO is doped with Ce and Mn. The Nb 3d peaks of NNO and MC-NNO show that ( Figure 2 (c and e), the two peaks of Nb after doping move to lower binding energy, indicating that doping destroys the original crystal structure and increases the electron density of Nb. Figure 2The results show that the oxygen vacancies of NNO and MC-NNO are 12.14% and 31.23%, respectively, indicating that doping leads to an increase in the oxygen vacancy content of MC-NNO. Figure 2 g and h are the peaks of Mn 2p and Ce 3d in MC-NNO, respectively, indicating that there is Mn in MC-NNO. 2+ , Mn 4+ 、Ce 3+ and Ce 4+ .
[0074] Figure 3 The following is a schematic diagram of the PFM amplitude diagram, phase diagram, butterfly loop and phase hysteresis curve results of NNO and MC-NNO. Figure 3 a, b) and phase ( Figure 3 As shown in the images (c and d), both NNO and MC-NNO have piezoelectric effect. Figure 3 Figures e and f are schematic diagrams of the butterfly loop results of NNO and MC-NNO, respectively. Compared with NNO, MC-NNO produces a higher amplitude, indicating that it produces a larger strain under the electric field. The piezoelectric constants of NNO and MC-NNO are 36.87pm / V and 46.05pm / V, respectively. Phase hysteresis curve ( Figure 3 Figures g and h show that the phase hysteresis curve of MC-NNO is significantly narrower than that of NNO, showing a phase difference of 180°, indicating that it is easier to be polarized, that is, the piezoelectric performance is better. In summary, doping can significantly improve the piezoelectric properties of NNO, because doping increases crystal irregularity, distorts the lattice, and shifts the charge center, and doping reduces the electron screening effect and promotes electron transfer.
[0075] Figure 4 The figure is a schematic diagram of the EIS curves and transient acoustic current curves of NNO, M-NNO, C-NNO and MC-NNO. Figure 4 As shown in (a), compared with NNO, the curvature radius of the EIS curves of M-NNO, C-NNO and MC-NNO is smaller, among which MC-NNO has the smallest curvature radius, indicating that doping can reduce impedance and thus promote carrier migration. Figure 4 Figure b shows that compared with NNO, doping with Mn and Ce can increase the density of the sample's acoustic current. MC-NNO has the fastest ultrasonic responsiveness and the largest acoustic current density, indicating that doping can improve the separation and migration of carriers in the sample under ultrasound.
[0076] Figure 5The following is a schematic diagram of the UV-Vis-NIR diffuse reflectance spectra and Kubelka–Munk spectra of NNO, M-NNO, C-NNO and MC-NNO. Figure 5 (a) shows that compared with NNO, MC-NNO has a higher absorbance in the 200-800nm band, and C-NNO has a higher UV absorption capacity in the 200-350nm band. Among all samples, MC-NNO has the highest light absorption capacity. The bandgap width diagram of different samples calculated by Kubelka–Munk ( Figure 5 (be in the figure) shows that the bandgap of NNO is 3.39eV, the bandgap of M-NNO and C-NNO is 3.14eV and 3.35eV respectively, and the bandgap of MC-NNO is the lowest (3.06eV), indicating that doping Mn and Ce reduces the bandgap of MC-NNO. The mechanism of acoustic power is similar to that of photodynamics. Under the action of ultrasound, cavitation effect is generated. After the bubbles in the liquid burst, high temperature and high pressure are generated to cause sonoluminescence. After the semiconductor absorbs photons, it induces electron transition, so that redox reactions occur in the conduction band and valence band to induce ROS generation. Therefore, M-NNO, C-NNO and MC-NNO have lower bandgap and higher light absorption capacity, and their electrons and holes are easier to separate under ultrasound, and the acoustic power performance is higher.
[0077] Figure 6 This is a schematic diagram of the XPS valence band spectrum of NNO and MC-NNO. XPS valence band spectrum ( Figure 6 As shown in a and b, the valence bands of NNO and MC-NNO are 2.25eV and 1.72eV respectively, and doping causes the valence band to move upward. Based on the bandgap width and valence band, the conduction bands of NNO and MC-NNO are calculated to be -1.14eV and -1.34eV respectively.
[0078] 2. Characterization of the acoustic dynamic performance of the sample:
[0079] Rhodamine B (RhB) solution (10 mg / L) was used as a molecular probe of total ROS to characterize the sonodynamic properties of different samples and the relationship between the sonodynamic properties and ultrasonic power.
[0080] The 1 mg / mL sample was placed in 10 mL of RhB solution and irradiated with ultrasound (1.5 W / cm 2 , 1MHz, 10min), and then the UV-Vis absorption spectrum of the solution was characterized by a UV-Vis spectrometer; the sample with the best acoustic dynamic performance was subjected to different ultrasonic powers (0.3, 0.5, 0.8, 1, 1.5W / cm 2, 1 MHz) for 10 min, and the UV-Vis absorption spectrum of the solution after ultrasound was measured.
[0081] Methylene blue (MB) solution (5 mg / L) and 1,3-diphenylisobenzofuran (DPBF) solution (10 mg / L) were used as hydroxyl radicals (·OH) and superoxide anions (·O2 - ) indicator, characterizing the relationship between sonodynamic performance and ultrasonic time.
[0082] The results were measured at different ultrasound times (0, 2, 4, 6, 8, 10 min, 1.5 W / cm 2 , 1 MHz) after the UV-Vis absorption spectra of MB solution and DPBF solution.
[0083] 5,5-Dimethyl-1-pyrroline N-oxide (DMPO) was used as ·OH (water system) and ·O2 - The capture agent of (methanol system) was used to measure the sample under ultrasound (1.5W / cm 2 , 1MHz, 10s) to produce ·OH and ·O2 - ability.
[0084] Figure 7 This is a schematic diagram of the sonodynamic mechanism of the sample. As can be seen from the figure, ultrasound induces MC-NNO to generate a built-in electric field, which promotes the separation of electrons and holes. The VB of MC-NNO is more negative than the redox potential of H2O / ·OH (+2.10 eV), which is not conducive to ·OH. However, under the action of the piezoelectric field, the valence band bends, causing the holes to accumulate toward the potential that is conducive to the generation of ·OH. The conduction band of MC-NNO is more negative than that of O2 / ·O2 - The redox potential of MC-NNO is more negative, so MC-NNO has the ability to generate ·OH and ·O2 - ability.
[0085] Figure 8 The figure is a schematic diagram of the effect of different Mn and Ce doping amounts on the acoustic dynamic performance of the sample. RhB was used as an indicator of ROS to measure the effect of different Mn and Ce doping amounts on the acoustic dynamic performance of the sample in order to optimize the doping content. The results show that Mn doping can improve the acoustic dynamic performance of NNO. When the Mn doping amount is 4 mol%, the acoustic dynamic performance of M4-NNO is the best ( Figure 8 Ce doping can improve the acoustic dynamic performance of NNO. When doped with 4 mol% Ce, the acoustic dynamic performance of C4-NNO is optimal ( Figure 8 (as shown in b). Figure 8 Figure c is a schematic diagram of the acoustic dynamic performance results of different samples. Compared with M4-NNO and C4-NNO, MC-NNO has higher acoustic dynamic performance, indicating that the acoustic dynamics of the double-doped modified sample is better than that of the single-doped sample.
[0086] Acoustic dynamic test of MC-NNO at different ultrasonic powers ( Figure 8 The results shown in (d) show that: under low power ultrasound (0.3W / cm 2 and 0.5W / cm 2 ), MC-NNO hardly produces ROS; when the ultrasonic power reaches 0.8W / cm 2 When the ultrasonic power is high, the sonodynamic performance of MC-NNO can be stimulated to produce ROS. The higher the ultrasonic power, the higher the sonodynamic performance of the sample. MB and DPBF were used as indicators to detect the generation of ·OH( Figure 8 (shown in e) and O2 - ( Figure 8 The relationship between ·OH and ·O2 produced by MC-NNO increases with the increase of ultrasonic time. - Constantly increasing.
[0087] 3. Characterization of sample morphology and enzyme-like activity
[0088] 3.1 Digital photos and SEM analysis
[0089] The MC-NNO images were taken using a camera, and the morphology of MC-NNO was characterized using a scanning electron microscope (SEM, S4800, Hitachi, Japan).
[0090] 3.2 Characterization of POD-like activity
[0091] TMB (3,3',5,5'-tetramethylbenzidine) was used as a detection reagent for the POD-like activity of the samples.
[0092] A sample (10 mg) with a concentration of 1 mg / mL was added to a 10 mL mixed solution of TMB (0.6 mM) and hydrogen peroxide (3 mM). The volume ratio of TMB to hydrogen peroxide was 1:1. At pH = 5.5, the UV-Vis absorption spectra of different samples after reacting with the above solution for 10 min were measured. The optimal enzyme activity sample was measured at different ultrasonic powers (0, 0.3 W / cm 2 , 0.5W / cm 2 , 0.8W / cm 2 , 1.0W / cm 2 , 1.5W / cm 2 ) was reacted with TMB solution for 10 min to characterize the effect of ultrasound on POD-like activity; the UV-Vis absorption spectrum of the sample with the best enzyme activity was measured under different pH (2-8) conditions after reacting with TMB solution for 10 min to characterize the pH dependence of the POD-like activity of the sample.
[0093] 3.3 CAT activity assay
[0094] The catalase activity (CAT) of the samples was measured using a portable dissolved oxygen meter.
[0095] The sample (50 mg) with a concentration of 1 mg / mL was added to 50 mL of 10 mM H2O2 solution, and different pH values (4.5, 5.5, 6.5, 7.4) and ultrasonic powers (0, 0.3 W / cm 2 , 0.5W / cm 2 , 0.8W / cm 2 , 1.0W / cm 2 , 1.5W / cm 2 ), and the content of dissolved oxygen in the solution was measured every 5 min within 1 h using a portable dissolved oxygen meter (AR8406, Wanchuang Electronic Manufacturing Co., Ltd.) to characterize the amount of oxygen produced.
[0096] 3.4 Characterization of piezoelectric properties of samples
[0097] The piezoelectric properties of NNO and MC-NNO were measured by piezoelectric force microscopy (PFM, NTEGRA, NT-MDT, Russia). 2 The ITO conductive glass was used as the bottom electrode. The conductive AFM probe in the PFM experiment was coated with Ti / Ir. The butterfly loop and phase hysteresis curves were obtained in the dual AC resonance tracking PFM (DART-PFM) mode. During this process, single-point spectral measurements were performed.
[0098] Through quasi-static 33 The piezoelectric constants of different samples were tested by a measuring instrument (ZJ-4, Beijing Jingke Zhichuang Technology Development Co., Ltd.). Before the test, the samples needed to be polarized by a piezoelectric polarization device (PZT-JH10 / 4, Beijing Jingke Zhichuang Technology Development Co., Ltd.).
[0099] The oscilloscope (TBS1102C, Tektronix, USA) was used to measure the conductivity of different samples under external ultrasonic stimulation (0.5 W / cm 2 , 1MHz), and the short-circuit current of the sample under ultrasonic stimulation was processed by an amplifier (SR570, Stanford, USA) and tested by an oscilloscope.
[0100] 3.5 Antimicrobial characterization of samples
[0101] The in vitro antibacterial properties were characterized by Gram-positive Staphylococcus aureus (ATCC 29213, S. aureus) and Gram-negative Escherichia coli (ATCC 25922, E. coli).
[0102] S. aureus and E. coli were cultured in tryptone soy broth (TSB) and lysogeny broth (LB) medium, respectively, and cultured in a 37°C incubator for 12 hours before use.
[0103] The samples were divided into four groups: (1) MPC group; (2) MPC+H2O2+US group; (3) MPC / MCN-2 group; (4) MPC / MCN-2+H2O2+US group;
[0104] MPC group: The samples were sterilized by ultraviolet irradiation for 12 h. The bacterial suspension (1×10 6 CFU / mL, 1 mL) was mixed with samples (500 μg / mL) in a 24-well plate and co-cultured for 6 h.
[0105] MPC+H2O2+US group: The samples were sterilized by ultraviolet irradiation for 12 h. The bacterial suspension (1×10 6 CFU / mL, 1 mL) was mixed with samples (500 μg / mL) and H2O2 solution (10 mM) in a 24-well plate and cultured for 6 h. 2 , 1MHz) for 10min.
[0106] MPC / MCN-2 group: The samples were sterilized by ultraviolet irradiation for 12 h. The bacterial suspension (1×10 6 CFU / mL, 1 mL) was mixed with samples (500 μg / mL) in a 24-well plate and co-cultured for 6 h.
[0107] MPC / MCN-2+H2O2+US group: The samples were sterilized by ultraviolet irradiation for 12 h. The bacterial suspension (1×10 6 CFU / mL, 1 mL) was mixed with samples (500 μg / mL) and H2O2 solution (10 mM) in a 24-well plate and cultured for 6 h. 2 , 1MHz) for 10min.
[0108] Bacterial colony count and antibacterial rate: Wash the sample with PBS three times to remove unattached bacteria. Then, immerse the sample in 2 mL of PBS and separate the bacteria on the sample surface by ultrasonic vibration. After diluting 10 times, spread 20 μL of bacterial suspension on a nutrient agar plate and incubate at 37 ° C for 24 hours. Take pictures of the colonies with a digital camera and count them, and calculate the antibacterial rate using the following formula:
[0109]
[0110] Where N C is the MPC falling number, N B is the colony number of other groups.
[0111] 3.6 Characterization of osteoblast response to magnesium-based bone cement
[0112] Cell culture: Rat bone marrow stromal cells (BMSC) were used in cell experiments. 10vt% fetal bovine serum (FBS, Gibco, USA) and 1vt% penicillin-streptomycin (Tianjin Haoyang Biological Products Technology Co., Ltd.) were added to α-MEM culture medium (Tianjin Haoyang Biological Products Technology Co., Ltd.), and the culture medium was placed in a cell culture incubator with a CO2 concentration of 5%, a humidity of 100%, and a temperature of 37°C. The culture medium was changed every 3 days. Samples of BMSC cultured to passages 3-5 were inoculated in 24-well plates (cell density was 3×10 4 During the culture process, ultrasound was applied at low power (0.5 W / cm 2 , 1MHZ) twice a day, treating the cells for 20 s each time.
[0113] Cell proliferation: Cell counting kit (CCK-8) was used to detect the proliferation of cells on the sample. After the cells were cultured on the material surface for different time periods (1, 3 and 7 days), the old culture medium was discarded and slowly rinsed with PBS. CCK-8 was added to each well and incubated for 1 hour. The supernatant was transferred to a new 96-well plate and the OD value of the solution was obtained at 450nm using an ELISA reader.
[0114] Fig. 9 The ESR spectra of ·OH and ·O2 produced by different samples - ESR spectrum diagram; pH = 5.5, US = 1.5 W / cm 2 . Fig. 9 a and b show that compared with NNO, MC-NNO produced ·OH and ·O2 - The signal peak of MC-NNO is stronger, indicating that the sonodynamic performance of MC-NNO is better; when H2O2 is added, MC-NNO can produce ·OH, which is attributed to the POD-like activity of MC-NNO; under the combined action of H2O2 and ultrasound, MC-NNO exerts sonodynamic and POD-like activity to produce more ·OH; and MC-NNO has CAT-like activity and can produce O2, providing a substrate for sonodynamics, thereby increasing ·O2 - The production of.
[0115] Fig.10Schematic diagram of the CAT activity (a) and POD activity (d) of different samples at pH = 7.4 and pH = 5.5, the CAT activity (b) and POD activity (e) of MC-NNO at different pH values, and the CAT (c, pH = 7.4) and POD (f, pH = 5.5) activities at different ultrasonic intensities.
[0116] CAT-like activity of different samples ( Fig.10 The test results (shown in a) show that under the action of H2O2, M-NNO, C-NNO and MC-NNO can produce O2, indicating that they have CAT-like activity, among which MC-NNO has stronger CAT-like activity. The CAT activity of MC-NNO was measured under different pH conditions, such as Fig.10 As shown in (b), as the pH increases, the CAT activity of the sample increases. The effect of ultrasound on the CAT activity of MC-NNO was determined. Fig.10 As shown in c, when the external ultrasonic power is less than or equal to 0.5W / cm 2 When the ultrasonic power increases, the CAT activity of the sample increases; when the ultrasonic power reaches 0.8W / cm 2 When the power is 100 W and above, the sonodynamic properties of MC-NNO are stimulated, and the oxygen in the system is consumed, resulting in a lower oxygen content in the system than under low-power ultrasound.
[0117] The POD-like activity of different samples was detected using TMB as an indicator ( Fig.10 The results show that compared with NNO, the absorbance of TMB in M-NNO, C-NNO and MC-NNO groups is higher, indicating that after doping with Mn and Ce, the samples have POD-like activity, among which MC-NNO has the highest POD-like activity. Fig.10 Figure e shows that under alkaline conditions, MC-NNO produces almost no ·OH. When the pH decreases, the POD-like activity of MC-NNO increases. The effect of ultrasound on the POD-like activity of MC-NNO was determined ( Fig.10 The results show that when the ultrasonic power is less than or equal to 0.5W / cm 2 As the ultrasonic power increases, the ability of the sample to produce ·OH increases. When the ultrasonic power reaches 0.8 W / cm 2 When the sonodynamic properties of MC-NNO are activated and the ability of the sample to produce ·OH is significantly enhanced.
[0118] In summary, MC-NNO has POD-like and CAT-like activities, which is attributed to the Mn 4+ and Mn 2+ and Ce 4+ and Ce 3+Under the action of ultrasound, MC-NNO will generate a built-in electric field to promote electron transfer, thereby improving the conversion of the valence state of the elements and further improving the dual enzyme activity of MC-NNO.
[0119] Fig.11 Figure 1 is a digital photo and SEM image diagram of magnesium-based bone cement MPC / MCN-2 particles, where a is a digital photo of magnesium-based bone cement particles. It can be seen from the figure that they are cylindrical and uniform in size. It can be observed that a porous structure is formed on the surface of magnesium-based bone cement particles after immersion, and the pore distribution is relatively uniform; bd is the surface morphology of magnesium-based bone cement porous particles at different magnifications. It can be seen that the holes on the particle surface are approximately circular, and the pore size distribution is in the range of 300-400μm. The enlarged picture shows that an interlaced mesh structure is formed on the particle surface, which is the morphology of magnesium-based bone cement after curing.
[0120] Fig.12 Figure 1 is a schematic diagram of the acoustic dynamic performance of magnesium-based bone cements with different compositions, where a is a schematic diagram of the acoustic dynamic performance of magnesium-based bone cements with different compositions; b is a schematic diagram of the relationship between the acoustic dynamic performance of MPC / MCN-2 and ultrasonic power; c is a schematic diagram of the acoustic dynamic performance of MPC / MCN-2 at 1.5 W / cm 2 Schematic diagram of the generation of ·OH under ultrasound, d is MPC / MCN-2 at 1.5W / cm 2 Ultrasonication produces O2 - Schematic diagram of the time-dependent results. It can be seen from the figure that the sonodynamic performance of the magnesium-based bone cement sample MPC / MCN-2 is the best, and it is less than or equal to 0.5W / cm 2 When the ultrasonic power is 0.8W / cm 2 When the ultrasonic power increases, the sample exerts its acoustic dynamic performance, and as the ultrasonic power increases, the acoustic dynamic performance of MPC / MCN-2 is optimal ( Fig.12 As the ultrasonic time increases, the sample continues to produce ·OH and ·O2 - ( Fig.12 (as shown in c and d).
[0121] Fig.13Schematic diagram of the activity data results of magnesium-based bone cements with different components at pH = 7.4, wherein a is a schematic diagram of the CAT activity data results of magnesium-based bone cements with different components at pH = 7.4, b is a schematic diagram of the CAT activity data results of MPC / MCN-2 at different pH values, c is a schematic diagram of the CAT (pH = 7.4) activity data results at different ultrasonic intensities, d is a schematic diagram of the POD activity data results of magnesium-based bone cements with different components at pH = 5.5, e is a schematic diagram of the POD activity data results of MPC / MCN-2 at different pH values, and f is a schematic diagram of the POD activity data results of MPC / MCN-2 at different ultrasonic intensities (pH = 5.5). After adding MC-NNO to magnesium-based bone cement, the sample has a CAT-like ( Fig.13 (shown in a) and POD-like activity ( Fig.13 As shown in (d); and as the MC-NNO content increases, the enzyme-like activity of magnesium-based bone cement increases. As the pH increases, the CAT-like activity of MPC / MCN-2 increases ( Fig.13 (b), POD-like activity decreased ( Fig.13 and the piezoelectric effect generated by ultrasound can enhance the activity of its dual enzymes ( Fig.13 (as shown in c and f).
[0122] Fig.14 Different samples at 0.5W / cm 2 Schematic diagram of the data results of open circuit voltage and short circuit current under ultrasound, where a is the value of different samples at 0.5W / cm 2 Schematic diagram of the open circuit voltage data under ultrasound, b is the open circuit voltage of different samples at 0.5W / cm 2 Schematic diagram of the data results of short-circuit current under ultrasound. It can be seen from the figure that under ultrasound, MPC has no obvious current and voltage signals; MPC / N-2 and MPC / MCN-2 have voltage and current signals of ultrasound response, and the electrical signal of MPC / MCN-2 is the highest, with an open circuit voltage and short circuit current of 0.64V and 533μA respectively; this is because the piezoelectric properties of MC-NNO are higher than those of NNO.
[0123] Fig.15The figure is a schematic diagram of the results of in vitro antibacterial performance after culturing different samples and different culture conditions, among which a is a schematic diagram of the colony photo of S. aureus, b is a schematic diagram of the colony photo of E. coli, c is a schematic diagram of the antibacterial rate results for S. aureus; d is a schematic diagram of the antibacterial rate results for E. coli. The figure shows the removal effect of the samples on bacteria. The results show that without H2O2 and ultrasonic treatment, a large number of bacteria survived in the MPC group and the MPC / MCN-2 group; after H2O2 and ultrasonic treatment, the bacteria in the MPC+H2O2+US and MPC / MCN-2 groups were reduced to a certain extent compared with the MPC group, indicating that simple ultrasonic treatment or the addition of simple manganese / cerium doped sodium niobate piezoelectric materials only has weak antibacterial properties, while the bacteria in the MPC / MCN-2+H2O2+US group were significantly reduced, indicating that under the action of ultrasound, MPC / MCN-2 has excellent antibacterial properties. The antibacterial rates of S. aureus and E. coli were 92±2.08% and 97±1.77%, respectively, indicating that the piezoelectrically enhanced sonodynamics and enzyme-like activity of MPC / MCN-2 synergistically produced ROS, which could effectively kill bacteria.
[0124] Fig.16 Schematic diagram of the effect of different components of magnesium-based bone cement on the proliferation of rat bone marrow stromal cells (BMSC); US = 0.5W / cm 2 As can be seen from the figure, without ultrasound, among all the components, MPC / MCN-2 has the strongest effect on promoting BMSC proliferation; after ultrasound treatment, the cells in the MPC group are roughly the same as those in the non-ultrasound group, which is attributed to the fact that MPC does not have piezoelectricity; due to the mechanical force of ultrasound, MPC / N-2 is induced to generate electrical signals, so it can promote the further proliferation of BMSC cells; compared with MPC / N-2, MPC / MCN-2 has higher piezoelectric properties, so under the action of ultrasound, cell proliferation is significantly enhanced.
[0125] The present invention prepares sodium niobate co-doped with manganese and cerium by a hydrothermal method, and the doping gives MC-NNO piezoelectrically enhanced enzyme-like activity, and improves its sonodynamic and piezoelectric properties. When added to magnesium-based bone cement, the magnesium-based bone cement has piezoelectrically enhanced sonodynamic and enzyme-like activity, synergistically kills bacteria and removes biofilms; and can promote osteoblast proliferation through ultrasound-activated piezoelectric effect. Therefore, the magnesium-based bone cement has both antibacterial and osteogenic functions, and is expected to be used in the clinical treatment of bone defects.
[0126] The above is only a preferred embodiment of the present invention, and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment, it is not used to limit the present invention. Any technician familiar with this patent can make some changes or modify the technical contents suggested above into equivalent embodiments without departing from the scope of the technical solution of the present invention. However, any simple modification, equivalent change and modification made to the above embodiments according to the technical essence of the present invention without departing from the content of the technical solution of the present invention still fall within the scope of the solution of the present invention.
Claims
1. A manganese-cerium co-doped modified sodium niobate, characterized in that: It is made of Nb2O5, MnO2, CeO2 and sodium hydroxide, the molar ratio of Nb2O5, MnO2 and CeO2 is 1:0.01-0.2:0.01-0.2; the molar ratio of Nb2O5 and sodium hydroxide is 1:1-50.
2. A method for preparing the manganese-cerium co-doped modified sodium niobate according to claim 1, characterized in that: The method comprises the following steps: grinding and mixing Nb2O5, MnO2 and CeO2 in a molar ratio of 1:0.01-0.2:0.01-0.2 evenly, dissolving in a sodium hydroxide solution with a concentration of 1-5 mol / L, wherein the molar ratio of Nb2O5 to sodium hydroxide is 1:1-50, stirring to a uniform suspension, reacting at a temperature of 150-200°C for 1-16 hours, washing, drying and calcining to obtain the manganese-cerium co-doped modified sodium niobate.
3. The method for preparing manganese-cerium co-doped modified sodium niobate according to claim 2, characterized in that: The drying conditions are as follows: drying at a temperature of 50 to 80° C. for 1 to 24 hours.
4. The method for preparing manganese-cerium co-doped modified sodium niobate according to claim 2, characterized in that: The calcination conditions are as follows: calcination at a temperature of 350 to 500° C. for 0.5 to 2 hours.
5. A magnesium-based bone cement with both sonodynamic / nanozyme antibacterial and piezoelectric osteogenesis, characterized in that: The invention is prepared from CaHPO4, NaH2PO4, MgO powder, hydroxyapatite and the manganese-cerium co-doped modified sodium niobate according to claim 1, wherein the molar ratio of CaHPO4, NaH2PO4 and MgO is 1-4:1-4:1, the mass of hydroxyapatite accounts for 5-20wt% of the total mass of CaHPO4, NaH2PO4 and MgO, and the mass of manganese-cerium co-doped modified sodium niobate accounts for 5-40wt% of the total mass of CaHPO4, NaH2PO4, MgO, hydroxyapatite and manganese-cerium co-doped modified sodium niobate.
6. A method for preparing magnesium-based bone cement with both sonodynamic / nanozyme antibacterial and piezoelectric osteogenesis as claimed in claim 5, characterized in that: The invention comprises the following steps: mixing CaHPO4, NaH2PO4 and MgO powders in a molar ratio of 1 to 4:1 to 4:1, adding hydroxyapatite and mixing evenly, wherein the mass of hydroxyapatite accounts for 5 to 20 wt% of the total mass of CaHPO4, NaH2PO4 and MgO, mixing the mixed powder obtained above evenly with sodium niobate modified by co-doping with manganese and cerium, wherein the mass of sodium niobate modified by co-doping with manganese and cerium accounts for 5 to 40 wt% of the total mass of CaHPO4, NaH2PO4, MgO, hydroxyapatite and sodium niobate modified by co-doping with manganese and cerium, adding deionized water so that the liquid-solid ratio is 1.5 to 3 g / mL, fully blending, filling into a mold for molding, and solidifying to obtain the magnesium-based bone cement with both sonodynamic / nanozyme antibacterial and piezoelectric osteogenesis.
7. The method for preparing magnesium-based bone cement with both sonodynamic / nanozyme antibacterial and piezoelectric osteogenesis according to claim 6, characterized in that: The curing conditions are as follows: the sample is placed in an incubator at a temperature of 37° C. and a humidity of 100% for curing for 1 to 72 hours.
8. Use of the magnesium-based bone cement with both sonodynamic / nanozyme antibacterial and piezoelectric osteogenesis as claimed in claim 5 in the preparation of bone repair scaffolds.
9. Use of the magnesium-based bone cement having both sonodynamic / nanozyme antibacterial and piezoelectric osteogenesis as claimed in claim 5 in the preparation of bone repair materials or bone transplant materials.
Citation Information
Cited By
Biphasic bioactive tissue repair scaffold and preparation method thereof
CN120365051A
Bone repair material as well as preparation method and application thereof
CN120518122A
Manganese-bismuth co-doped niobium oxide material as well as preparation method and application thereof
CN120518123A